Exercise as cancer treatment: A clinical oncology framework for exercise oncology research - Courneya, Kerry S.; Booth, Christopher M. (Frontiers in Oncology, 2022)
Exercise has been proposed as a possible cancer treatment; however, there are an infinite number of clinical oncology settings involving diverse cancer types and treatment protocols in which exercise could be tested as a cancer treatment. The primary purpose of this paper is to propose a conceptual framework to organize and guide research on exercise as a cancer treatment across distinct clinical oncology settings. A secondary purpose is to provide an overview of existing exercise research using the proposed framework. The Exercise as Cancer Treatment (EXACT) framework proposes nine distinct clinical oncology scenarios based on tumor/disease status and treatment status at the time of the proposed exercise treatment. In terms of tumor/disease status, the primary tumor has either been surgically removed (primary goal to treat micrometastases), not surgically removed (primary goal to treat the primary tumor), or metastatic disease is present (primary goal to treat metastatic disease). In terms of treatment status, the extant disease has either not been treated yet (treatment naïve), is currently being treated (active treatment), or has previously been treated. These two key clinical oncology variables—tumor/disease status and treatment status—result in nine distinct clinical oncology scenarios in which exercise could be tested as a new cancer treatment: (a) treatment naïve micrometastases, (b) actively treated micrometastases, (c) previously treated micrometastases, (d) treatment naïve primary tumors, (e) actively treated primary tumors, (f) previously treated primary tumors, (g) treatment naïve metastatic disease, (h) actively treated metastatic disease, and (i) previously treated metastatic disease. To date, most preclinical animal studies have examined the effects of exercise on treatment naïve and actively treated primary tumors. Conversely, most observational human studies have examined the associations between exercise and cancer recurrence/survival in patients actively treated or previously treated for micrometastases. Few clinical trials have been conducted in any of these scenarios. For exercise to be integrated into clinical oncology practice as a cancer treatment, it will need to demonstrate benefit in a specific clinical setting. The EXACT framework provides a simple taxonomy for systematically evaluating exercise as a potential cancer treatment across a diverse range of cancer types and treatment protocols.